Do tourists' personality traits moderate the relationship between social media content sharing and destination involvement?. Issue 5 (13th June 2019) - Dedeoglu, Bekir Bora; Okumus, Fevzi; Yi, Xiaoli; Jin, Wenmin
ABSTRACT: This study investigates how the importance attached to consumer-generated content on social media affects the destination involvement. This study also examines the moderating role of personality traits between social media content and destination involvement. Data was collected from 586 respondents. Study results suggest that the importance attached to participant sharing and the importance attached to non-participant sharing affect destination involvement in a positive and significant way. In addition, the impact of the importance attached to participant sharing on involvement is more determinant for individuals where agreeableness, extraversion, openness, and conscientiousness traits are high.